Two-Level Study of Object-Oriented Programming by University Students - Dmitrieva, T.A.; Prutzkow, A.V.; Pylkin, A.N. (Современные информационные технологии и IT-образование, 2019)
The difficulties of learning the paradigm of object-oriented programming by university students are considered. Two approaches to learn object-oriented programming: Object-First (learning this paradigm at the start of programming learning) and Object-Later (prior learning of structured and procedural programming) are described. The expediency to use the second approach consisting of two levels is proved. The requirements to knowledge and skills being necessary for object-oriented programming are formulated. A review of programming languages used in both levels is presented. The conclusions are made; recommendations to study object-oriented programming are given.